2006
DOI: 10.1142/s021773230602069x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transition in the Higgs Model of Scalar Dyons

Abstract: In the present paper we investigate the phase transition "Coulomb-confinement" in the Higgs model of abelian scalar dyons -particles having both, electric e and magnetic g, charges. It is shown that by dual symmetry this theory is equivalent to scalar fields with the effective squared electric charge e * 2 = e 2 + g 2 . But the Dirac relation distinguishes the electric and magnetic charges of dyons. The following phase transition couplings are obtained in the one-loop approximation: α crit = e 2 crit /4π ≈ 0.1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…The calculation of the critical coupling constants in the Higgs scalar monopole (dyon) model of dual U(1) theory [65,69,70]…”
Section: Three Generations Of Quark-leptons and Bosonsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calculation of the critical coupling constants in the Higgs scalar monopole (dyon) model of dual U(1) theory [65,69,70]…”
Section: Three Generations Of Quark-leptons and Bosonsmentioning
confidence: 99%
“…The calculation of the critical coupling constants in the Higgs scalar monopole (dyon) model of dual U(1) theory [65,69,70] gave the following results: According to Eqs. ( 48)-( 50), the condensation of spreons leads to the following critical constants:…”
Section: Three Generations Of Quark-leptons and Bosonsmentioning
confidence: 99%
“…In Refs. [28,32,41] and in Appendix B it was shown that when we consider the both, chromo-electric and chromo-magnetic (non-dual and dual), charges we can write the following general expressions for β-functions of the renormalization group equations (RGEs):…”
Section: Renormalization Group Equations and Dualitymentioning
confidence: 99%
“…Non-trivial topology (17) amounts to winding of elements of matrix (18), and we obtain string solutions:…”
mentioning
confidence: 99%
“…The calculation of the critical coupling constants in the Higgs scalar monopole (dyon) model of dual U(1) theory [16,17] gave the following result:…”
mentioning
confidence: 99%